Lattice dynamics and electron-phonon coupling in geometrically distorted halide double perovskites - Kanapathi, Prakash; Ravi, Nalini; Mohan, Subramaniam; Vijayan, Viswanathan; Appadurai, Tamilselvan (Journal of Physical Chemistry C, 2026)
Electron-phonon coupling is a critical factor in regulating the photophysical behavior of halide double perovskites (HDPs), influencing their emission broadening through lattice softness and exciton dynamics. In this work, we investigate four structurally distorted compounds, such as Cs2Ag0.4Na0.6InCl6, Cs2NaIn0.9Bi0.1Cl6, Cs2AgIn0.9Bi0.1Cl6, and Cs2Ag0.4Na0.6In0.9Bi0.1Cl6, prominent for their broad emission characteristics. Our combined experimental analysis and numerical models demonstrate that the electron-phonon coupling is dictated by the interplay between the sublattice distortion and the bonding nature between the metal and halide atoms, which vitally modulates the overall lattice softness and the resulting spectral broadening. The introduction of more ionic Na-Cl bonds in the HDP structure softens (weaker bonding) the lattice and enhances the phonon population, resulting in strong coupling between the electron and phonon, as quantified by the Huang-Rhys factor for Cs2NaIn0.9Bi0.1Cl6 (18.88), Cs2Ag0.4Na0.6InCl6 (17.64), and Cs2Ag0.4Na0.6In0.9Bi0.1Cl6 (14.46). Raman analysis further evidences Na-induced lattice softness with a 5 cm-1 red shift of the A1g mode in Cs2NaIn0.9Bi0.1Cl6, compared to Ag-containing HDPs. These findings highlight that Na-based compounds have stronger electron-phonon coupling than Cs2AgIn0.9Bi0.1Cl6. Furthermore, temperature-dependent phonon dynamics using the cubic anharmonic model and the three-phonon anharmonicity theory demonstrate that the distorted structures involve a phonon anharmonicity due to the thermal disorder. We show that strong coupling between the electron and the energetic phonon broadens the emission spectrum but suppresses the PL intensity. This quenching may arise from the excessive phonon-intervened nonradiative relaxations in the Na-rich compounds. By contrast, the temperature-dependent PL of Cs2Ag0.4Na0.6In0.9Bi0.1Cl6, a compound with maximum PL intensity, reveals the major contribution of optical phonon to electron-phonon coupling, which facilitated the efficient STE formation. This study highlights the significance of lattice softness to regulate the optoelectronic properties of the halide double perovskites, providing a design approach for compositional engineering towards high-performance optoelectronic devices.